Steroid Androgen Exposure during Development Has No Effect on Reproductive Physiology of Biomphalaria glabrata. - Satwant Kaur; Alice Baynes; Anne E Lockyer; Edwin J Routledge; Catherine S Jones; Leslie R Noble; Susan Jobling (PLoS ONE, 2016)
Gastropod mollusks have been proposed as alternative models for male reproductive toxicity testing, due to similarities in their reproductive anatomy compared to mammals, together with evidence that endocrine disrupting chemicals can cause effects in some mollusks analogous to those seen in mammals. To test this hypothesis, we used the freshwater pulmonate snail, Biomphalaria glabrata, for which various genetic tools and a draft genome have recently become available, to investigate the effects of two steroid androgens on the development of mollusk secondary sexual organs. Here we present the results of exposures to two potent androgens, the vertebrate steroid; 5α-dihydrotestosterone (DHT) and the pharmaceutical anabolic steroid; 17α-methyltestosterone (MT), under continuous flow-through conditions throughout embryonic development and up to sexual maturity. Secondary sexual gland morphology, histopathology and differential gene expression analysis were used to determine whether steroid androgens stimulated or inhibited organ development. No significant differences between tissues from control and exposed snails were identified, suggesting that these androgens elicited no biologically detectable response normally associated with exposure to androgens in vertebrate model systems. Identifying no effect of androgens in this mollusk is significant, not only in the context of the suitability of mollusks as alternative model organisms for testing vertebrate androgen receptor agonists but also, if applicable to other similar mollusks, in terms of the likely impacts of androgens and anti-androgenic pollutants present in the aquatic environment.